How to write a successful cover letter, not one that sinks you - Canavor, Natalie 1942- (Pearson Education Pub. as FTPress Delivers, 2010)
"This Element is an excerpt from The Truth About the New Rules of Business Writing (ISBN: 9780137153152) by Natalie Canavor and Claire Meirowitz. When employers ask for cover letters (even with online applications) along with your credentials, they mean it--they want a letter, not a spontaneous-looking e-mail or text message. They will most definitely judge you on it. This is perfectly fair. Employers want to see how you handle yourself in writing: the better you can, the more of an asset you'll be"--Resource description page.
Keywords: Cover letters; Business writing; Business communication; Business report writing; Lettres d'introduction; Style commercial; Communication dans l'entreprise; BUSINESS & ECONOMICS; Management; BUSINESS & ECONOMICS; Reference; BUSINESS & ECONOMICS; Skills; Commerce; Business & Economics; Vocational Guidance